Measuring Geography Online Learning in The First Year Using The Online Learning Quality Index Based on Teachers and Learners’ Perceptions (OLQ-TLP) - Yulianto, Agung; Mukminan; Oktavianto, Dwi Angga; Widodo, Edi; Ramos, Angelou O. (Department of Geography Education, University of Jember, 2024)
Online learning is a relatively new thing for some teachers in South Kalimantan. It was the first time for these teachers to do online learning since the government took the policy of learning from home due to the disaster emergencies and environmental change. This study aims (1) to determine the perception of geography teachers in South Kalimantan who have just done online learning for the first time, and (2) to determine the quality of online learning that has been implemented based on the mean index value of each factor. The research was designed with a quantitative approach through an online survey of 26 geography teachers who teach 10th grade at the high school level. The sample was selected by Cluster Random Sampling. The questionnaire instrument used a modified the online learning quality index based on teachers and learners’ perceptions (OLQ-TLP). The research time was from December 2020 to February 2021. The results showed that teachers' perceptions of online learning were in a good category. Based on the index value, factors that have good quality are Learner content, Learner interaction, Instruction interaction, Social Presence, and Course design. Other factors still need to be improved, namely the factors of Learner satisfaction, Knowledge acquisition, Learning platform, Instruction, Learning support, and Ability of transfer. Therefore, to improve teachers' expertise in online geography learning on lithosphere material, training with an innovative Digital Education Shifting (DES) approach is needed.